Maintaining and Developing Ethical Corporate Culture - Moslem Soleymanpor (Journal of Global Pharma Technology, 2017)
Of  all  the  issues  boards  of  directors,  executives,  and  managers  face,  one could  argue  that  unethical  corporate  activity  is  one  of  the  most  signiﬁcant  in  terms  of its  potential  negative  impact  and  also  one  of  the  most  difﬁcult  to  properly  address. This  article  argues  that  three  key  elements  must  exist  if  illegal  or  unethical  activity within  and  on  behalf  of  organizations  is  to  be  minimized  through  developing  and sustaining  an  ethical  corporate  culture.  The  three  elements  include  (1)  the  existence of  a  set  of  core  ethical  values  infused  throughout  the  organization  in  its  policies, processes,  and  practices;  (2)  the  establishment  of  a  formal  ethics  program,  including a  code  of  ethics,  ethics  training,  an  ethics  hotline,  and  an  ethics  ofﬁcer;  and  (3)  the continuous  presence  of  ethical  leadership-that  is,  an  appropriate  ‘tone  at  the  top’  as reﬂected  by  the  board  of  directors,  senior  executives,  and  managers.  While  each  of these  three  elements  is  distinct,  they  also  overlap,  relate  to,  and  reinforce  each other.  This  article  discusses  each  of  the  three  key  elements  necessary  to  develop  and maintain  an  ethical  corporate  culture. Keywords: Ethical corporate culture; Ethical values; Ethics programs; Ethical  leadership.